2008
DOI: 10.1242/jeb.008193
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a silicatein(-related) protease in the giant spicules of the deep-sea hexactinellidMonorhaphis chuni

Abstract: SUMMARYSilicateins, members of the cathepsin L family, are enzymes that have been shown to be involved in the biosynthesis/condensation of biosilica in spicules from Demospongiae (phylum Porifera), e.g. Tethya aurantium and Suberites domuncula. The class Hexactinellida also forms spicules from this inorganic material. This class of sponges includes species that form the largest biogenic silica structures on earth. The giant basal spicules from the hexactinellids Monorhaphis chuni and Monorhaphis intermedia can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
43
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 58 publications
7
43
0
Order By: Relevance
“…Therefore, we used both E-64 and phenylmethylsulfonyl fluoride (PMSF) as inhibitors in the reaction assay. E-64 inhibited directly the processing of the cathepsin-related silicatein, as expected (data not shown) (31), while the maturation of prosilicatein to silicatein proceeded in the presence of PMSF. PMSF is known to be an effective inhibitor of thrombin protease (39), however, only for a very limited period of time (about 1 h) (32) and surely not for 24 h as seen in our assays 3 .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Therefore, we used both E-64 and phenylmethylsulfonyl fluoride (PMSF) as inhibitors in the reaction assay. E-64 inhibited directly the processing of the cathepsin-related silicatein, as expected (data not shown) (31), while the maturation of prosilicatein to silicatein proceeded in the presence of PMSF. PMSF is known to be an effective inhibitor of thrombin protease (39), however, only for a very limited period of time (about 1 h) (32) and surely not for 24 h as seen in our assays 3 .…”
Section: Discussionsupporting
confidence: 86%
“…Silicatein cleavage has been proposed to proceed either by autolysis (29) or by a second protease (30). Since the processing of the S. domuncula pro-silicatein-␣ to silicatein-␣ can be prevented by the incubation with 5 M E-64 3 , an irreversible inhibitor of a wide range of cysteine peptidases, including silicatein from the hexactinellid Monorhaphis chuni (31), an autocatalytic cleavage process is most likely.…”
Section: Silicatein-trigger Factor Fusion Protein-silicatein Was Exprmentioning
confidence: 99%
“…The silicateins are assembled into a linear fiber (28,29) that is found within the core of demosponge spicules and catalyze silica formation via a hydrolysis pathway from organically functionalized silicic acid precursors at neutral pH (8,9,11). In addition to their discovery in several other demosponge species (12-18), silicateins or silicatein-like proteins have also been reported from hexactinellid sponges such as M. chuni and C. meyeri (19)(20)(21). If silicatein exists in Euplectella, as is suggested based on partial cDNA data [GenBank accession no.…”
Section: Discussionmentioning
confidence: 99%
“…Müller et al (19)(20)(21) reported that antibodies against silicatein α from the demosponge Suberites domuncula cross-reacted with a 27-kDa protein in the giant anchor spicules of Monorhaphis chuni and with a 24-kDa protein in the spicules of Crateromorpha meyeri. Mass spectrometric analysis of a fragment from the M. chuni 27-kDa protein demonstrated that it contained sequences corresponding to the silicateins from demosponges (22).…”
mentioning
confidence: 99%
See 1 more Smart Citation